Credit Risk of Islamic Banks in GCC Countries - Hamid A. H. Al-Wesabi; Nor Hayati Ahmad (The International Journal of Banking and Finance, 2013)
This paper is about factors affecting credit risk of Islamic banks in the Gulf Cooperation Council countries using website data covering 25 Islamic banks over 2006 to 2010. This study uses non-performing loans as a proxy for credit risk, which is the dependent variable with three macro-economic, and six firm-specific independent variables. We find income is significantly negatively related to credit risk, which is consistent with findings in other countries about credit risk. Some firm-specific variables such as leverage, liquidity are also relevant variables for credit risk, which results are also consistent with bank behaviour reported in other studies. Credit risk is also broadly affected by both macro and firm-specific factors as found in other regions. Inflation and interest rates do not appear to be relevant. These results would suggest non-performing loan is broadly correlated with factors identified in other studies of banks.